Effects of single‐case reading interventions for students with and at‐risk of emotional and behavioral disorders in grades K–12: A quantitative synthesis. Issue 4 (15th February 2019) - McKenna, John William; Shin, Mikyung; Solis, Michael; Mize, Min; Pfannenstiel, Kathleen
Abstract: This study examined the effects of reading interventions from single‐case design studies for students with and at‐risk of emotional and behavioral disorders in grades K–12 using a quantitative synthesis. Seventeen studies met the selection criteria of having one more dependent variables meeting what works clearinghouse (WWC) design standards with or without reservations. Although students' reading performance significantly improved from baseline to intervention phases ( p  < 0.001), the overall weighted average effect size was weak (Tau‐ U  = 0.58, 95% confidence interval = [0.54, 0.63]; d  = 0.29); smaller effects were found on reading comprehension. Interventions were less effective for students in secondary grades, students with a comorbid disability, and students in substantially separate settings. While no studies meeting the selection criteria were conducted in inclusive settings, the teacher provided interventions were more effective than those provided by researchers suggesting the importance of the student–teacher relationship for reading instruction. Study limitations, areas for future research, and implications for school practices are discussed.